1062 Problematic drinking behaviour among belgian workers: prevalence, health and job related consequences. (24th April 2018) - Lambrechts, Marie-Claire; Vandersmissen, Lieve; Godderis, Lode
Abstract : Introduction: Only few data on the (problematic) use of alcohol in workers and possible job related effects are available. Methods: In 2016 an anonymized questionnaire was filled out by Belgian employees while waiting for a periodical occupational health screening. The Alcohol Use Disorders Identification Test- Consumption (AUDIT-C) was used to measure prevalence of alcohol consumption. Also, the effects on absenteeism, lost productivity, workplace accidents, conflicts with co-workers and sanctions by employers were investigated. Result: 5367 workers completed the questionnaires. 37.1% of last year drinkers (n=4197) drank more than once a week; 36.4% with an average daily consumption of 3 to 4 units, 11.4% with ≥5 to 6 units. Respectively 22.7% and 7.8% exhibited binge drinking at least once a month/week. Based on AUDIT-C 39.1% of last year drinkers had an indication of problematic drinking. This was significantly higher among higher educated and male employees<35 years. In the construction industry, 51.6% of last year drinkers had an indication of problem drinking. 12.2% of last year drinkers experienced consequences on the job. 27.8% observed negative effects among their colleagues, especially being late at work (18.3%), irregular job performances (18%), absenteeism (15.7%) and conflicts with colleagues (10.6%). There is a significant relation between the AUDIT-score and job related effects (p<0, 001). Being single, age (<35 year) and specific work environments were risk factors: 23.5% of workers within the construction industry, 17.8% within the catering industry and 17.1% within the transport sector experienced consequences at the workplace in the past year. We did not found correlations between the AUDIT-C score and job stress, satisfaction, recognition and variation. Discussion: Overall results show that problem drinking among workers is a typically male issue. Given the negative impact of work, a tailored and multicomponent alcohol policy in different sectors need to be implemented.